Upaya Menjadi Kepala Sekolah yang Sukses (Studi Empiris di SMA IT Nurul Ilmi Kota Jambi) - Muspawi, Mohamad; Viola, Mayshel Adinda; Vilanti, Friska Aqilah; Rahman, Indah Afidah; Masita, Masita (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract : This article is entitled Efforts to Become a Successful Principal at Nurul Ilmi IT High School, Jambi City. The principal is an educator who is authorized or officially appointed as the principal, who is given the mandate and responsibility to empower and set an example to all school members in order to improve the quality of the school. The school principal is required to be a figure who must be able to act as a mediator who can make decisions, resolve problems and be a source of information for the school community he leads. Educational progress is also determined by the success and leadership of the school principal. The success and leadership success of a school principal in his activities is influenced by factors that can support leadership success, including the goals that will be achieved if there is harmony in relationships, both relationships and interactions between superiors and subordinates. Apart from being influenced by the leader's experience as a personal motivation for success, maturity and freedom in social relationships are also factors that can support leadership success and success. The main topic of discussion in this article is how to become a successful school principal. This research uses qualitative methods with data collection techniques through interview methods and literature review. The results of the interview were as expressed by the principal Integrade Islamic High School Nurul Ilmi, Jambi City, he revealed several steps that could be considered to improve leadership skills in order to achieve success and success as a principal, including: giving the best, accepting criticism and input from various parties, and overcome various obstacles that exist at school. Key Words : Headmaster, Leadership, Success. School Abstrak : Artikel ini berjudul Upaya Menjadi Kepala Sekolah yang Sukses di SMA IT Nurul Ilmi Kota Jambi. Kepala sekolah merupakan seorang tenaga pendidik yang berwenang atau ditunjuk secara resmi sebagai kepala sekolah, yang diberikan amanah dan tanggung jawab memberdayakan dan memberi contoh kepada seluruh warga sekolah guna meningkatkan mutu sekolah. Kepala sekolah dituntut menjadi sosok yang harus mampu berperan sebagai mediator yang dapat mengambilan keputusan, menyelesaian masalah dan menjadi sumber informasi bagi warga sekolah yang dipimpinnya. Kemajuan pendidikan juga ditentukan oleh keberhasilan dan kesuksesan kepemimpinan kepala sekolah. Keberhasilan dan kesuksesan kepemimpinan seorang kepala sekolah dalam kegiatannya dipengaruhi oleh faktor-faktor yang dapat menunjang keberhasilan kepemimpinan, antara lain tujuan yang akan dicapai apabila terjalin keselarasan dalam hubungan, baik hubungan atau interaksi antar atasan dengan bawahan. Selain dipengaruhi oleh pengalaman pemimpin sebagai motivasi pribadi untuk sukses, kedewasaan dan keleluasaan dalam hubungan sosial juga merupakan faktor yang dapat menunjang keberhasilan dan kesuksesan kepemimpinan. Adapun pokok pembahasan dalam artikel ini yaitu bagaimana upaya menjadi kepala sekolah yang sukses. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data melalui metode wawancara dan tinjauan kepustakaan. Hasil wawancara seperti yang diungkapkan oleh kepala Sekolah Menengah Atas Islam Terpadu (SMA IT) Nurul Ilmi Kota Jambi, beliau mengungkapkan beberapa langkah yang dapat dipertimbangkan guna meningkatkan keterampilan kepemimpinan guna mencapai keberhasilan dan kesuksesan sebagai kepala sekolah diantaranya : berikan yang terbaik, menerima kritik dan masukan dari berbagai pihak, serta mengatasi berbagai kendala yang ada di sekolah. Kata Kunci : Kepala sekolah, Kepemimpinan, Kesuksesan, Sekolah.